STUDI PEMISAHAN Co(II), Cu(II), Fe(III) DAN Ni(II) SECARA EKSTRAKSI PELARUT DENGAN ZAT PENGKOMPLEKS NATRIUM DIETILDITIOKARBAMAT - Soefjan Tsauri; K. Anom W; Buchari Buchari (Research Center for Chemistry - LIPI, 1993)
Sodium diethyldithiocarbamate (NaDDC) as a chelating agent reacts unselectively with cobalt(II), copper(II), iron(III) and nickel(II). Their maximum wavelengths are very similar in carbon tetrachloride solution and hence these complexes could not be determined by UV/VIS spectrophotometer without prior separation. A scheme of separation has been found for qualitative analysis of cobalt(II), copper(II), iron(III) and nickel(II) at a certain pH using a specific masking agent. It was found that pH 9 turned out to be the best condition for iron(III) masking but neither for cobalt(II), nor for copperill] and nickel(II). The addition of 10 mL HCI 12 N to the complex solutions of Co(II), Cu(II) and Ni(II) would remove Cu(II) and Ni(II) complexes from CC14 to water phase whereas Co(II) complex was still in the CCl4 phase. Cu(II) and Ni(II) ions in the water phase were then treated with 10 mL Titriplex 8,66 x 10-5 mole at pH 9 in which Ni(II) was masked but not Cu(II).